(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
The purposes of the research were 1) to develop and test the efficiency of English Reading Exercises(ERE) in Thematic English (E20202) for grade 9 students of Princess Chulabhorn’s College Phitsanulok (PCCPL) according to standard criteria 75/75, 2) to compare the students’ English reading competency before and after using ERE in E20202, and 3) to survey the students’ satisfactions toward them. The subjects consisted of the randomly selected class of 23grade 9 students of PCCPL during the first academic year 2014. The instruments used for this experiment were 6 units of the ERE in E20202, lesson plans for the ERE in E20202, pre-test and post-test of 6 units which were objective tests consisted of 4 alternatives in the ERE in E20202, the English reading proficiency test and a questionnaire on the subjects’ satisfactions toward the ERE in E20202. The results of the study were as follows: 1) the efficiency of the ERE in E20202 was 82.54 for the English reading formative test and 85.22 for the post-test. Therefore, the ERE in E20202 constructed were highly effective, 2) the students’ English reading proficiency after using the ERE in E20202 was significantly higher than that before using the ERE in E20202 constructed at 0.01 level, 3) the students’ satisfactions toward the ERE in E20202 were very highly satisfied.